Cranial versus Caudal Direction Technique of Native Percutaneous Kidney Biopsy: A Randomized Controlled Trial - Jaturapisanukul S; Chavanisakun C; Benjakul N; Ngamvichchukorn T; Laungchuaychok P; Kurathong S; Pongsittisak W (International Journal of Nephrology and Renovascular Disease, 2023)
Solos Jaturapisanukul,1,2 Chutima Chavanisakun,3 Nontawat Benjakul,3 Tanun Ngamvichchukorn,1 Punnawit Laungchuaychok,1 Sathit Kurathong,1,2 Wanjak Pongsittisak1,2 1Division of Nephrology and Renal Replacement Therapy, Department of Internal Medicine, Faculty of Medicine Vajira Hospital, Navamindradhiraj University, Bangkok, Thailand; 2Vajira Renal-Rheumatology-Autoimmune Disease Research Group, Bangkok, Thailand; 3Department of Anatomical Pathology, Faculty of Medicine Vajira Hospital, Navamindradhiraj University, Bangkok, ThailandCorrespondence: Wanjak Pongsittisak, Tel +66818345228, Email wanjak@nmu.ac.thBackground: Percutaneous kidney biopsy (PKB) is the gold standard for diagnosing various kidney diseases, but it can result in potential complications. This study aimed to compare kidney tissue adequacy and safety between the two biopsy techniques, including cranial direction (CN) and caudal direction (CD), of needle biopsy under real-time ultrasonogram guidance.Methods: This single-center, prospective, single-blinded, randomized trial included patients undergoing native PKB from July 5, 2017, to June 30, 2019. Patients were randomized to the CN and CD groups. Adequacy and complications between the two groups were analyzed. All PKBs were performed under real-time ultrasonogram guidance with a 16-gauge kidney biopsy needle.Results: A total of 107 participants were enrolled (53 in the CD group and 54 in the CN group). The CD group has more glomeruli than the CN group but with no statistical significance (16 versus 11, p = 0.0865). The CD group obtained more adequate kidney tissue samples than the CN group (69.8% versus 59.3%, p = 0.348). The number of inadequate glomeruli tissue sampling is similar in both groups (14 versus 15, respectively). Furthermore, the CN group had more adverse events, including Hb decline ≥ 10% after kidney biopsy, perinephric hematoma size ≥ 1 cm, hematuria, and the need for blood transfusion, than the CD group.Conclusion: The CD technique of the percutaneous kidney biopsy in the native kidney has fewer complications and was possibly more effective than the CN technique.Keywords: kidney biopsy, needle trajectory, post-biopsy complication